Detailed characterization of the cooperative binding of piperine with heat shock protein 70 by molecular biophysical approaches - Zazeri, Gabriel [UNESP]; Povinelli, Ana Paula Ribeiro [UNESP]; Lima, Marcelo de Freitas [UNESP]; Cornélio, Marinônio Lopes [UNESP] (MDPI, 2020)
In this work, for the first time, details of the complex formed by heat shock protein 70 (HSP70) independent nucleotide binding domain (NBD) and piperine were characterized through experimental and computational molecular biophysical methods. Fluorescence spectroscopy results revealed positive cooperativity between the two binding sites. Circular dichroism identified secondary conformational changes. Molecular dynamics along with molecular mechanics Poisson Boltzmann surface area (MM/PBSA) reinforced the positive cooperativity, showing that the affinity of piperine for NBD increased when piperine occupied both binding sites instead of one. The spontaneity of the complexation was demonstrated through the Gibbs free energy (∆G < 0 kJ/mol) for different temperatures obtained experimentally by van’t Hoff analysis and computationally by umbrella sampling with the potential of mean force profile. Furthermore, the mean forces which drove the complexation were disclosed by van’t Hoff and MM/PBSA as being the non-specific interactions. In conclusion, the work revealed characteristics of NBD and piperine interaction, which may support further drug discover studies.
Keywords: Fluorescence spectroscopy; Heat shock protein 70; Hsp70; Molecular biophysics; Molecular docking; Molecular dynamics; Piperine